Fabrication of forward osmosis membrane using nata-de-coco as raw materials for desalination - Bautista-Patacsil, Liza (Animo Repository, 2020)
© 2020. A Forward Osmosis (FO) membrane was fabricated using a locally available material nata de coco (NDC) to form a bacterial cellulose (BC) film. Sodium alginate was used to form composites with the BC film. Two concentrations (10% and 15%) of cross-linking agent, CaCl2, were compared in terms of its performance as a FO membrane for application in desalination. Two salts were compared as draw solution: 2M sucrose (C12H22O11) and 2M magnesium chloride (MgCl2). The performance of the fabricated NDC-FO membrane was investigated in terms of water flux, salt flux and percent salt rejection in a laboratory-scale FO system. The 15% CaCl2 solution was observed to give high water flux, low salt flux, and high salt rejection compared to the 10% CaCl2. The 15% CaCl2 solution produced a more tensile membrane compared to 10% CaCl2, one endures pressure at the suction points of the FO module while the other breaks after some time of operation, respectively. The NDC-FO membrane has an average contact angle of 14.137° with an average thickness of 0.159 mm. The 2M MgCl2 performs better than sucrose as a draw solution. The commercial Cellulose Tri-Acetate (CTA) FO membrane was used to benchmark the performance of NDC-FO membrane. The NDC-FO membrane produces a water flux of 4.01 LMH with 88.39% salt rejection, which is comparable to the water flux of CTA with 7.97 LMH and 100% salt rejection. Results showed the potential of nata de coco as raw material for FO membrane.